Employee Perception Analysis of The Use Fingerprint Attendance System at Department of Manpower and Transmigration of Southeast Minahasa - Sefryan Reinaldo Uway; Sifrid S. Pangemanan; Shinta J.C. Wangke (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
Currently technology is also used in various work activities, one of which is the attendance system. Attendance is an activity or routine carried out by employees to prove that they are present or not present at work in a company. This attendance relates to the application of discipline determined by each company or institution. The purpose of this study is to find out the employee perception of the usage of fingerprint absence system, in this case within the employees of Department of Manpower and Transmigration of Southeast Minahasa. This study uses a qualitative method and interview toward informants were conducted in order to gain information regarding the phenomenon. The findings of this study show that the current system is better than the previous system in terms of usability and convenience, behavior changes because employees become more disciplined at work and are quite effective in reducing the risk of fraud. Based on the result, there are several recommendations which are maintenance regarding the machine that used by the employees and giving reward toward employees that can maintain one hundred percent rate of entering the office on time to boost the morale of the employees.Keywords: Employee Perception, Fingerprint Absence System